Terms of Trade Shocks and Economic Recovery - Imam, Patrick; Funke, Norbert; Granziera, Eleonara (Washington, D.C. : International Monetary Fund, 2008)
This paper identifies factors that contribute to a fast recovery in growth after persistent negative terms of trade shocks, using a sample of 159 countries for 1970-2006. The results suggest that policies matter. Fast recoveries are fairly robustly related to real exchange rate depreciation and improvements in government stability and the institutional environment. A timely increase in aid may also support recovery.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet